Australia's developmental trajectory: Neoliberal or not?. (July 2014) - Higgins, Vaughan
General support is given for Weller and O'Neill's (2014) aim to question the influence of neoliberalism on political and economic change in Australia. However, their key proposition that Australia's developmental trajectory has never been neoliberal in intent or outcome is challenged. Critiqued also is Weller and O'Neill's use of a working definition of neoliberalism that fails to engage explicitly or sufficiently with theoretical perspectives on neoliberal governance. A governmentality approach is argued to offer a way forward in exploring how neoliberal and non-neoliberal rationalities and techniques articulate with one another as part of attempts to address specific problematizations of rule.